(3EjVGM GdaJGhi aj GdfcJ GdeJYdbI HGdMGhjs - (3GdfGTQj , YHO Gddg Hf eMeO Hf YHO Gddg Hf YeQ Hf CHh HcQ Hf YeQ, CHh GdaJhM,J (B814 (3g` s
(3ChdgG (B:s
(3HGH GddYGf s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs